Micro‐ and macro‐optimizations of SaaT search. (20th February 2019) - Trotman, Andrew; Crane, Matt
Summary: We introduce and test several micro‐ and macro‐optimizations to the Score‐at‐a‐Time approach to processing impact‐ordered postings lists in a search engine. Our micro‐optimizations are at the single‐assembly instruction level, but our macro‐optimizations are algorithmic. Overall, we see an improvement of 37% on our baseline (22% on state of the art). We experiment with parallel search and present evidence that we have hit the memory wall.